2016
DOI: 10.1016/j.jmgm.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Open source molecular modeling

Abstract: The success of molecular modeling and computational chemistry efforts are, by definition, dependent on quality software applications. Open source software development provides many advantages to users of modeling applications, not the least of which is that the software is free and completely extendable. In this review we categorize, enumerate, and describe available open source software packages for molecular modeling and computational chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 182 publications
0
50
0
Order By: Relevance
“…Open source software packages for molecular modelling and computational chemistry (Pirhadi, Sunseri & Koes, 2016) could be used for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Open source software packages for molecular modelling and computational chemistry (Pirhadi, Sunseri & Koes, 2016) could be used for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, JavaScript interpreters in web browsers have improved dramatically, and now enable use of graphics applications directly within a web browser. There are a growing number of efforts aimed at developing JavaScript/WebGL based 3D viewers (13). RCSB PDB has supported JSmol (JSmol: an open-source HTML5 viewer for chemical structures in 3D, http://wiki.jmol.org/index.php/JSmol) and PV (14) for some time, and recently added support for NGL.…”
Section: New Website Featuresmentioning
confidence: 99%
“…The Made Smarter Review of 2017 identified that adopting digital prediction in industrial workflows could streamline economical and material overheads in manufacturing. One barrier to the adoption of such technology can be the usability and the ease of understanding of the software developed , . Recent publications have highlighted promising workflows, where molecular modeling approaches appraise solution and particle chemistry of organic materials .…”
Section: Introductionmentioning
confidence: 99%